Cooperation Between The Cimahi Police Criminal Investigation Unit and the Banking Sector in Disclosing Social Engineering Cases - Tono Listianto; Chairul Muriman Setyabudi; Sutrisno Sutrisno (Ridwan Institute, 2023)
Information technology is increasingly advanced, coupled with the existence of the internet, which is now a global communication system that allows everyone around the world to meet and talk about almost anything. The internet has become a medium of communication, which is done through various media available on it. The internet provides various social media platforms, both for positive and negative reasons, and has become the order of the day because nowadays, the world is so tied to the internet. Unfortunately, not everyone uses the internet for a good cause. There are many people who use social networks to commit crimes, such as cyber-crime in the form of social engineering. Social engineering allows malicious hackers to gain unauthorized access to an organization's networks, user accounts and emails, databases, smart devices, and electronics, such as laptops, personal webcams, and sensors, including network connectivity that allows all of these objects to exchange data. These hackers use a variety of methods to carry out social engineering attacks. The technical complexity of the information systems used in locating, examining, and analyzing relevant transaction data requires sufficient time and technical expertise to gather robust evidence to support the case for social engineering, which involves in-depth analysis of bank transaction data related to the attack. This process can be time-consuming, especially if many transactions need to be traced and analyzed.